Worms, bacteria and micronutrients: an elegant model of our diet - Yilmaz, L. Safak (Trends Genet, 2014)
Micronutrients are required in small proportions in a diet to carry out key metabolic roles for biomass and energy production. Humans receive micronutrients either directly from their diet or from gut microbiota that metabolize other nutrients. The nematode Caenorhabditis elegans and its bacterial diet provide a relatively simple and genetically tractable model to study both direct and microbe-mediated effects of micronutrients. Recently, this model has been used to gain insight into the relationship between micronutrients, physiology and metabolism. In particular, two B-type vitamins, vitamin B12 and folate, have been studied in detail. Here we review how C. elegans and its bacterial diet provide a powerful interspecies systems biology model that facilitates the precise delineation of micronutrient effects and the mechanisms involved.